RETRACTION: The genome sequence of the horse’s hoof clam, Hippopus hippopus (Linnaeus, 1758) - Ruiqi Li; Jingchum Li; Jose Victor Lopez; Graeme Oatley; Isabelle Ailish Clayton-Lucey; Elizabeth Sinclair; Eerik Aunin; Noah Gettle; Camilla Santos; Michael Paulini; Haoyu Niu; Victoria McKenna; et al. (Wellcome Open Research, 2025)
4 th December 2025: The article by Li R, Li J, Lopez JV et al. The genome sequence of the horse’s hoof clam, Hippopus hippopus (Linnaeus, 1758) [version 1; peer review: 3 approved with reservations] Wellcome Open Research 2024, 9 :131 ( https://doi.org/10.12688/wellcomeopenres.21137.1 ) has been retracted from Wellcome Open Research by the Editorial Team. After the data was published, it was discovered that the species sequenced was not Hippopus hippopus , but a member of the Tridacna genus. The accompanying data record was suppressed.